Newborn in the Pediatric Emergency Department: A Reality During the Covid-19 Pandemic - Aguiar, Bárbara (2022)
Background: Early neonatal hospital discharges are an important issue in perinatal care. We aimed to characterize newborns admitted to the Pediatric Emergency Department (PED) in the first months of the Covid-19 pandemic. Methods: We conducted a retrospective observational study concerning newborns who presented to the PED during the pandemic period, in comparison with the same period of the previous year. Data gathered concerning neonatal characteristics included length of postpartum stay in the nursery, age at presentation to the PED, source of referral to the PED, presenting complaint, need for complementary exams, diagnosis, final destination and hospital readmission. Results: We analyzed 72 PED admissions which constituted the contemporary cohort and 123 PED admissions which constituted the historical cohort. The rate of newborns discharged from the nursery before completing 36 hours of life was higher during the pandemic period. We found an increased rate of neonates visiting the PED in this period, especially during the first two weeks of life. There was a higher referral rate to the PED and higher rates of newborns referred to an ambulatory pediatrics appointment. No differences were found concerning the presenting complaints, need for complementary exams, diagnoses and admission rates. Discussion: Although there was an increased rate of neonatal admissions to the PED during the pandemic period, the severity of illness did not increase. The decreased time of parental education during the postpartum stay in the nursery and the reduced access to primary care during the pandemics might have been the major cause for the increased PED utilization. Keywords: Newborn; Early Neonatal Discharge; Primary Care; Emergency Service; Coronavirus; Pandemics.